Developing narrative writing skills via a reading programme for low English Language proficiency undergraduates - Tengku Sepora Tengku Mahadi,; Fauzilah Md Husain,; Paramaswari Jaganathan,; Arbaeyah Hassan,; Sharifah Nur Hamizah Syed Fesal,; Akmar Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper investigates the effects of a reading programme on the narrative writing skills of low English Language proficiency level undergraduates in a Malaysian university. A total of eighteen narrative texts closely associated with the undergraduates’ personal experiences were prepared by the researchers for a reading-writing intervention programme. This quasiexperimental study involved 192 undergraduates who participated in a nine-week intervention programme. The pre-test and post-test mean scores indicated significant differences in the undergraduates’ content development, lexical variety and grammatical accuracy. The findings show that there is an improvement in content, lexical variety and grammatical accuracy in students’ essays. The undergraduates’ improvement in the content development aspect shows that reading texts which supplement information common to the undergraduates’ background will help them in their content development specifically and writing performance on the whole. The study also shows that the reading materials, vocabulary input and comprehension exercises helped the undergraduates to improve on their use of lexical variety and grammatical structure. The results support the notion that comprehensible input (Krashen, 1984) and appropriate language instructional exercises for writing intervention enable engaged learning by the students. The study therefore recommends that teachers should utilise authentic reading materials that are relevant to the background knowledge of the students in teaching writing to low English proficiency level undergraduates.